Entrapping Instantly‐Cleaved CPT Prodrugs in Polymeric Micelles for CPT Delivery. Issue 42 (14th November 2019) - Liu, Fuyue; Li, Anqin; Li, Fu; Li, Jin; Yan, Lu; Li, Feng; Luo, Jing; Huang, Zhao; Zheng, Yaxin
Abstract: As the direct entrapment of camptothecin (CPT) into conventionally used polymeric materials is extremely difficult due to its high crystallization property, CPT‐derived prodrugs are widely used to increase drug‐polymer compatibility. However, the rapid CPT conversion from prodrugs is still a challenge due to the high steric hindrance around the hydroxyl of CPT. To address this, we reported here a fragile lactyl carbonate (LC) linker, which could be instantly cleaved to release CPT from LC‐linked lipophilic prodrugs under physiological conditions. Furthermore, such instantly‐cleaved CPT prodrugs could be stably encapsulated in methoxy poly(ethylene glycol)‐block‐poly(actic acid) (mPEG‐PLA) micelles, thus to achieve indirect CPT entrapment with a potent in vitro cytotoxicity as a result of the rapid CPT conversion. The strategy of entrapping instantly‐cleaved prodrugs in polymeric micelles displayed an excellent potential to broaden the scope of application of polymeric materials in drug delivery. Abstract : Lactyl carbonate (LC)‐linked camptothecin (CPT) prodrugs could be immediately converted into active CPT under physiological conditions, which provided a foundation for the rational design of instantly‐cleaved CPT prodrugs for the efficient CPT loading in conventionally used polymeric materials, such as poly(ethylene glycol)‐block‐poly(actic acid) (mPEG‐PLA). This strategy not only improved the encapsulation efficiency of CPT in polymeric micelles but also overcame the limitation of insufficient and slow CPT conversion from prodrugs once released from micelles.